Arginine methylation controls the strength of γc-family cytokine signaling in T cell maintenance. (November 2018) - Inoue, Maia; Okamoto, Kazuo; Terashima, Asuka; Nitta, Takeshi; Muro, Ryunosuke; Negishi-Koga, Takako; Kitamura, Toshio; Nakashima, Tomoki; Takayanagi, Hiroshi
Abstract The methylation of arginine residues in proteins is a post-translational modification that contributes to a wide range of biological processes. Many cytokines involved in T cell development and activation utilize the common cytokine receptor γ-chain (γc) and the kinase JAK3 for signal transduction, but the regulatory mechanism that underlies the expression of these factors remains unclear. Here we found that the arginine methyltransferase PRMT5 was essential for the maintenance of invariant natural killer T cells (iNKT cells), CD4+ T cells and CD8+ T cells. T cell–specific deletion ofPrmt5 led to a marked reduction in signaling via γc-family cytokines and a substantial loss of thymic iNKT cells, as well as a decreased number of peripheral CD4+ T cells and CD8+ T cells. PRMT5 induced the symmetric dimethylation of Sm proteins that promoted the splicing of pre-mRNA encoding γc and JAK3, and this critically contributed to the expression of γc and JAK3. Thus, arginine methylation regulates strength of signaling via γc-family cytokines by facilitating the expression of signal-transducing components. PRMT arginine methyltransferases mediate post-translational modification. Takayanagi and colleagues show that a lack of PRMT5 in cells of the T cell lineage compromises their response to cytokines dependent on the common γ-chain, due to aberrant splicing of mRNA transcripts encoding the common γ-chain and its associated kinase JAK3.